2005
DOI: 10.1111/j.1572-0241.2005.40899.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chronic Treatment with Octreotide versus Octreotide plus Midodrine on Systemic Hemodynamics and Renal Hemodynamics and Function in Nonazotemic Cirrhotic Patients with Ascites

Abstract: Octreotide does not improve systemic hemodynamics in nonazotemic cirrhotic patients with ascites while it impairs renal function. On the other hand, the addition of midodrine can ameliorate the hyperdynamic circulation without inducing renal dysfunction in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 42 publications
1
73
1
Order By: Relevance
“…Table 5 summarises all human data on the effects of somatostatin or octreotide on kidney function. Somatostatin and octreotide have been described in healthy subjects and patients with diabetes mellitus and acromegaly to decrease renal plasma flow (RPF) and concomitantly decrease glomerular filtration rate (GFR) with an unchanged filtration fraction [25][26][27][28][29][30][31][32]. However, it should be noted that some of these studies administered supraphysiological doses of somatostatin [100-420 μg/h intravenously (IV) or 600 μg/day subcutaneously (SC)].…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 summarises all human data on the effects of somatostatin or octreotide on kidney function. Somatostatin and octreotide have been described in healthy subjects and patients with diabetes mellitus and acromegaly to decrease renal plasma flow (RPF) and concomitantly decrease glomerular filtration rate (GFR) with an unchanged filtration fraction [25][26][27][28][29][30][31][32]. However, it should be noted that some of these studies administered supraphysiological doses of somatostatin [100-420 μg/h intravenously (IV) or 600 μg/day subcutaneously (SC)].…”
Section: Discussionmentioning
confidence: 99%
“…In type 1 HRS, alpha-1 agonists have only been used in combination with other agents. Few nonrandomized, prospective studies have evaluated treatment with both midodrine and octreotide [45][46][47] . The study by Angeli [45] included only fi ve patients and showed that after 20 d of treatment, all patients had serum creatinine levels below 2 mg/dL.…”
Section: Other Results Commentsmentioning
confidence: 99%
“…Midodrine is an oral alpha adrenergic agonist and it is administered as an initial dose of 7.5 mg every eight hours (maximum 15g to eight hours) and octreotide could be administered as a continuous infusion with a dose of 50 mcg/hour or subcutaneous with a dose of 100-200 mcg/8 hours. In combination with midodrine and octreotide, albumin is given as an intravenous bolus with a starting dose of 1 g/kg (maximum 100 g) and a maintenance dose of 20-50 g. Midodrine in combination with octreotide and albumin improve systemic and renal hemodynamic status [28]. Norepinephrine is a general vasoconstrictor agent used in the intensive care unit and it is administered as an intravenous continuous infusion with a dose of 0.5-3 mg/hour.…”
Section: Hrs Treatmentmentioning
confidence: 99%